Ecoinovações no setor supermercadista: estudo no segmento atacarejo - Bravo, Cleyton Bonilha (2023)
Eco-innovations, within the limit of their effective implementation, results in a positive effect on the environment, regardless of any other economic and/or social gain that may arise. This kind of innovation has been presented as a valid and promising alternative to differentiation strategies and business opportunities for contemporary organizations. Eco-innovation has been studied in the academic world, in recent years, with more intensity in developing countries and the occurrence of these studies has been highlighted in industrial or service sectors, so it is important to bring to the discussion also another important sector of the economy of these countries, the trade. In this perspective, when analyzing Brazilian trade, the supermarket sector stands out and, within the supermarket sector, the cash and carry segment, which is today the main growth engine. Thus, this research has the general objective of investigating the relationships between the dimensions of eco-innovations adopted in the cash and carry segment and their determinants and barriers. Regarding the nature of the data and the approach to the problem, the research is characterized as quantitative and qualitative. As for the procedures, it is a documentary and field research. As for the purposes, the research has a descriptive and exploratory character. Data were collected through document analysis of available documents and through interviews and questionnaires applied to employees in key positions in dealing with the issue in focus, regarding the creation and implementation of eco-innovations in companies in the cash and carry segment. In the data analysis, document analysis, descriptive statistics and content analysis were used, using the Atlas.Ti software as support. The research concluded that the cash and carry segment has implemented eco-innovations in greater numbers in the Design dimension, followed by eco-innovations in the User dimension. These eco- innovations are more present due to the existing technology that facilitates their implementation and the low existence of barriers. The Design dimension has few relationships with barriers, limited to the lack of resources, and it is the dimension that showed the least relationship with the determinants, with the existing technological capacity being the one that had the most positive impact. The Governance dimension is the one that has the greatest relationship with the existing barriers in the segment, mainly in relation to the barrier described as a lack of suppliers oriented towards environmental issues. The User dimension is the one that has the greatest relationship with the determinants, with the motivation to seek new knowledge and environmental education training for employees being the determinants that most impact the dimension. In general, the segment is in the process of including eco-innovations and there is room to grow in new eco-innovations in the governance and product and service dimensions, which today are the least eco-innovations implemented.